PENGARUH EFEKTIVITAS PENERAPAN SIA, INSENTIF, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) RAYON KUTA - Ananda, Firda; Badera, I Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022DO - 10.24843/EEB.2022.v11.i08.p07, 2022)
An effectively implemented accounting information system can improve employee performance. However, a case occurred at PT. PLN, which experienced a drastic drop in performance, was caused by a plan to cut salaries. The decline in performance is certainly influenced by a lack of motivation at work. This study aims to provide empirical evidence related to effectiveness of the application of accounting information systems, incentives, and work motivation on employee performance. Questionnaires was handed to 39 employees of PT. PLN Bali Rayon Kuta, then analyzed by multiple linear regression. Results indicate that the effectiveness of accounting information systems has a significant effect on employee performance, incentives have no significant effect on employee performance, and work motivation has no significant effect on employee performance.